Perlindungan Hukum bagi Masyarakat Adat atas Hak Tanah dalam Perspektif Hukum Nasional - Monasari, Septiani; Edrisy, Ibrahim Fikma (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Land rights for indigenous communities are an integral part of human rights guaranteed by national law. However, in practice, the recognition and legal protection of indigenous land rights still face various challenges, including agrarian conflicts, inconsistencies between customary and national laws, and weak policy implementation. This study aims to analyze the legal protection of indigenous land rights within the national legal framework, identify obstacles to its implementation, and propose solutions to strengthen such protection. This research employs a normative-juridical method with a statutory and case study approach. The findings indicate that although various regulations, such as Article 18B(2) of the 1945 Constitution, the Basic Agrarian Law, and Constitutional Court decisions, provide a legal foundation for recognizing indigenous land rights, their implementation remains weak. The main challenges include the dualism of customary and national legal systems, overlapping land concessions, and limited access to justice for indigenous communities. To enhance legal protection for indigenous land rights, agrarian policy reforms that favor indigenous communities, increased participation in land management, and stronger collaboration between the government, civil society, and legal institutions are necessary. With these concrete measures, the legal protection of indigenous land rights can be more effectively upheld within the national legal system.